The Dynamic Evolution of Overseas Market Network of Chinese Enterprises: Agglomeration or Dispersion. (4th August 2021) - Chen, Ruo-Yu; Sun, Yi
Abstract : Based on the CEPII-BACI database and China Customs database from 2000 to 2011, this paper combines the degree of export experience of enterprises with their own trade network to study the differential effects of accumulated export experience on the dynamic evolution of enterprises' overseas market network structure and further explores it from the perspective of community and neighbors. The results of this study show the following. (1) The location choice of Chinese enterprises' overseas market depends significantly on the structure of export network constructed in the past and tends to choose regions with closer geographical and economic ties as export target countries. There is a significant path dependence effect. However, enterprises with rich export experience are no longer subject to the constraints of geographical space and will make the overseas market layout more "decentralized." (2) The decision making of export market location depends on the community distribution of export network. The path-dependent effect of export market layout in the export network community is significantly greater than that outside the community and tends to choose the intra-community region for overseas market layout. (3) The export network of adjacent enterprises has a significant impact on the location of enterprises' overseas market. However, enterprises with rich export experience are less dependent on the geographic network expansion effect of their neighbors and tend to choose markets with close economic links.